Fixed Point Results for Multivalued Maps in Metric Spaces with Generalized Inwardness Conditions. (21st February 2010) - Frigon, M.
Abstract : We establish fixed point theorems for multivalued mappings defined on a closed subset of a complete metric space. We generalize Lim's result on weakly inward contractions in a Banach space. We also generalize recent results of Azé and Corvellec, Maciejewski, and Uderzo for contractions and directional contractions. Finally, we present local fixed point theorems and continuation principles for generalized inward contractions.